Analysis of the Application of the Principle of Freedom of Contract in Home Ownership Credit Agreements in Karanganyar - Ayu Sholihah, Zuliana; Suraji, Suraji; Suryono, Arief (International Journal of Educational Research & Social Sciences, 2023)
Home Ownership Credit is an agreement that arises between the bank as the creditor and the customer as the debtor.The creditor provides services in the form of financing for the purchase of a house with the debtor paying in installments according to the chosen tenor. Interest in Home Ownership Credit is very high in the people of Karanganyar Regency, Central Java. The offer of a Home Ownership program that can be paid for by credit is the main reason Home Ownership Credit has such high interest in Karanganyar Regency. Apart from that, government support with several subsidies for Home Ownership Credit is also the reason. Home Ownership Credit will result in a credit agreement between the creditor, namely the bank, and the customer or debtor. Credit agreements are made to ensure legal certainty between the creditor and debtor. The credit agreement made by the bank is in the form of a standard agreement which then needs to be presented to the customer for approval. Clauses made unilaterally by banks result in unequal authority between banks and customers. The economic advantages possessed by banks mean that customers who need financing programs from banks must agree to the standard agreement. The standard agreement in the agreement for granting Home Ownership Credit is the result of the Principle of Freedom of Contract which is intended to ensure that agreements can be balanced. However, in reality, this implementation results in the dominance of one party, namely banking, which has economic advantages. The need factor is the main reason that causes customers to inevitably agree to the standard agreement even though the agreement in it is not balanced.